Estimating the Cost of Increasing Retention in Care for HIV-Infected Patients: Results of the CDC/HRSA Retention in Care Trial. (1st March 2015) - Shrestha, Ram K.; Gardner, Lytt; Marks, Gary; Craw, Jason; Malitz, Faye; Giordano, Thomas P.; Sullivan, Meg; Keruly, Jeanne; Rodriguez, Allan; Wilson, Tracey E.; Mugavero, Michael
Abstract : Background: Retaining HIV patients in medical care promotes access to antiretroviral therapy, viral load suppression, and reduced HIV transmission to partners. We estimate the programmatic costs of a US multisite randomized controlled trial of an intervention to retain HIV patients in care. Methods: Six academically affiliated HIV clinics randomized patients to intervention (enhanced personal contact with patients across time coupled with basic HIV education) and control [standard of care (SOC)] arms. Retention in care was defined as 4-month visit constancy, that is, at least 1 primary care visit in each 4-month interval over a 12-month period. We used microcosting methods to collect unit costs and measure the quantity of resources used to implement the intervention in each clinic. All fixed and variable labor and nonlabor costs of the intervention were included. Results: Visit constancy was achieved by 45.7% (280/613) of patients in the SOC arm and by 55.8% (343/615) of patients in the intervention arm, representing an increase of 63 patients (relative improvement 22.1%; 95% confidence interval: 9% to 36%; P < 0.01). The total annual cost of the intervention at the 6 clinics was $241, 565, the average cost per patient was $393, and the estimated cost per additional patient retained in care beyond SOC was $3834. Conclusions: Our analyses showed that a retention in care intervention consisting of enhanced personal contact coupled with basic HIV education may be delivered at fairly low cost. These results provide useful information for guiding decisions about planning or scaling-up retention in care interventions for HIV-infected patients.